KGB veikla sovietinės Lietuvos pramonės įmonėse 1965–1985 m. - Grybkauskas, Saulius (Genocidas ir rezistencija, 2009)
The article seeks, on the basis of the KGB archival material, to elucidate the activity of the Soviet security committee in the industrial enterprises, to evaluate the role of KGB as a certain player in the economic system, to reveal the change of the control in this field conducted by KGB.Intensive industrialization which took place in Soviet Lithuania predetermined the growth of attention of the regime to the industry and the activity of the plants. The KGB activity in the industrial enterprises is reflected by the search of new measures of impact of the Soviet power on the public in still more complicated political, social and economic realities. They are especially noticeable from the middle of the eighth decade: certain liberalization of the permits to work with secret documents, application of preventive measures “with the assistance of the public”, attraction of the heads and specialists of the enterprises to the groups of fight against foreign technical intelligence service witness that rude interference of KGB into the internal management of the enterprises was replaced by the more effective and flexible method of KGB work.A counter-intelligence character of KGB activity in the industry preconditioned its limits as a certain authority in the economic system. Counter-intelligence access did not allow the potential of the competent agency to be used efficiently: information, received from agents, was related inconsiderably to the interests of the whole economic system, with the essence of the planned system.
Keywords: KGB; sovietinė sistema; ekonomika; pramonė; komunistų partija